Supervision Management Academic Principal at SD IT Izzatul Islam - Saiman, Saiman; Sugiyo, Sugiyo; Supraptono, Eko (Educational Management, 2021)
The purpose of this study was to describe and analyze the management of the principal's academic supervision at SD IT Izzatul Islam Getasan. The supervisor (principal) provides academic supervision (assistance of professional skills) to teachers to improve teacher performance. Where the professional competence of teachers in the quality of learning at SD IT Izzatul Islam is still using conventional methods. The approach used in this research is qualitative with descriptive research methods. Data was collected by means of interviews, observation, and documentation. Informants in this study were principals and teachers. The results show that academic supervision is very important to improve teacher performance. Planning for the academic supervision of the principal at SD IT Izzatul Islam Getasan is (1) the principal prepares for academic supervision by preparing instruments and analyzing teacher needs by conducting conversations and asking teachers (2) making and determining goals and objectives in the implementation of academic supervision (3) make a schedule for the implementation of the academic supervision program that has been planned with the previous teacher.